2019
DOI: 10.1177/0093854819848793
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Power of Dynamic (vs. Static) Risk Factors in the Finnish Risk and Needs Assessment Form

Abstract: We estimated the predictive power of the dynamic items in the Finnish Risk and Needs Assessment Form ( Riski- ja tarvearvio [RITA]), assessed by caseworkers, for predicting recidivism. These 52 items were compared to static predictors including crime(s) committed, prison history, and age. We used two machine learning methods (elastic net and random forest) for this purpose and compared them with logistic regression. Participants were 746 men who had and 746 who had not reoffended during matched follow-up perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Both cohorts were tested with ML models, but for this review we consider only the 1977–1978 data excluding the Tollenaar’s 2019 study [ 32 ] because the 1980 cohort showed a worse calibration probability. The dynamic elements of the Finnish Risk and Needs Assessment Form (RITA) were used by Salo and colleagues [ 27 ] to predict general and violent recidivism. The sample included 746 men sentenced to a new term of imprisonment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both cohorts were tested with ML models, but for this review we consider only the 1977–1978 data excluding the Tollenaar’s 2019 study [ 32 ] because the 1980 cohort showed a worse calibration probability. The dynamic elements of the Finnish Risk and Needs Assessment Form (RITA) were used by Salo and colleagues [ 27 ] to predict general and violent recidivism. The sample included 746 men sentenced to a new term of imprisonment.…”
Section: Resultsmentioning
confidence: 99%
“…The sorting leads to four categories: general [ 22 , 23 , 24 , 28 , 31 , 32 ], sexual [ 31 , 32 ], violent [ 22 , 25 , 31 ] and all other recidivism. The last category includes studies that considered a specific type of crime [ 21 ] or referred only to males [ 27 ] or youth [ 26 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also previous researches of CB behavior based on general criminological theories. Three of these theories have a greater theoretical incidence on personal factors: the Theory of Tension, by Robert Agnew; the Social Cognitive Theory with its mechanisms of moral disassociation, by Albert Bandura; and Ajzen's Theory of Reasoned Action; and a fourth that affects aspects of opportunity: the Theory of Daily Activities [43][44][45].…”
Section: Frameworkmentioning
confidence: 99%